Postmortem Study of Thyroid Arteries in Bangladeshi People (Bangladesh Journal of Anatomy, 2009)
Context: Anatomical knowledge of vasculature is essential for successful thyroid surgery. Vascular anatomy of thyroid artery may vary. Study design: Descriptive type of study. Place & Period of study: Department of Anatomy, Dhaka Medical College from July 2003 to December 2004. Materials: Present study was performed on 57 thyroid gland. The samples were collected from unclaimed dead bodies that were under examination in the Department of Forensic Medicine of Dhaka Medical College, Dhaka. Methods: The samples were divided in groups. All samples of thyroid arteries were studied morphologically. Five (5) samples were transferred into aided dissection by common vermilion mixed melted paraffin wax. Result: Superior thyroid artery was most commonly originated from external carotid artery (male- 76.5% both right and left, female-91.3% right, 73.9% left), followed by bifurcation of common carotid artery (maleright 14.7%, left 20.6%, female- left 13%, right 0% and from common carotid artery (male 8.8% right, 2.9% left, female- 8.7% right, 13% left) at the level or above the level of upper border of thyroid cartilage. On the right side in 100% and 94.7% cases superior thyroid artery and inferior thyroid artery were originated as a single artery respectively. On the left side in 94.7% and 87.7% cases superior thyroid artery and inferior thyroid artery were originated as a single artery respectively. On the left side, double superior thyroid artery was present in 5.3% cases, double inferior thyroid artery was present in 1.8% cases. Inferior thyroid artery was found to be absent in 4.3% right side, 9.5% left side in female cases and 5.9% both right and left side in male cases. There was no significant (P>0.05) difference between the length of superior thyroid artery on the right and left side. But the length of inferior thyroid artery showed significant (p